Knowledge of Pregnant Women About the Importance of Fulfillment of Folic Acid in the Optimization of Fetal Development During Pregnancy at the Giopani Simbolon Clinic - Fatimah (PT Inovasi Pratama Internasional, 2023)
Prevalence rates per 1000 live births regarding folic acid fulfillment were reported in Native Americans (2.7%), Japanese (2.1%), African Americans (0.42%). The purpose of this study was to find out the knowledge of pregnant women about the importance of fulfilling folic acid during pregnancy at the Giopani Simbolon Am.Keb Midwife Clinic, Padangmatinggi Village, South Padangsidimpuan District in 2020. This type of research is descriptive using accidental sampling with 20 respondents. Data collection uses a questionnaire sheet, using primary and secondary data based on variables of knowledge, age, education, employment, parity, and sources of information. Based on the results of the study of 20 respondents, the majority lacked knowledge, namely 14 respondents (70%), based on age the majority was less, namely 10 respondents (50%), based on education the majority was lacking, namely 8 respondents (40%), based on work the majority was lacking, namely 10 respondents (50%), based on parity the majority was lacking, namely 8 respondents (40%), and based on information sources the majority was lacking, namely 11 respondents (55%). Based on the results of the study it can be concluded that the majority of pregnant women's knowledge about the importance of fulfilling folic acid is still lacking so it is expected that pregnant women will increase their knowledge about folic acid either through health workers, print media, and electronic media.